Exploring the agriculture-nutrition disconnect in India - Gillespie, Stuart; Kadiyala, Suneetha (International Food Policy Research Institute, 2011)
India is home to one-third of the world's undernourished children, with rates of child undernutrition remaining stubbornly high for decades. Undernutrition is widespread among adults, too; one-third of all Indian men and women are affected. At the same time, India is the second-fastest-growing economy in the world. Its economic growth, however, has been far less “pro-poor” than growth in other Asian countries such as China, Thailand, and Vietnam, where major strides to reduce child undernutrition have been made during similar periods of economic growth. Why has such progress somehow eluded India? What lies beneath the apparent paradox of simultaneous nutritional stagnation and sustained economic growth in India?